Sexual signaling under predation: attractive moths take the greater risks. (29th January 2014) - Cordes, Nils; Engqvist, Leif; Schmoll, Tim; Reinhold, Klaus
Lay Summary: Calling a mate can be dangerous for insects, but that does not stop attractive wax moths from singing even when they hear a bat call. Theoretically, unattractive males should take higher risks because they have less to lose, instead they behave more cautiously. A reason for this difference in behavior could be that attractive moths exhaust themselves quickly and try to find a mate while they still can. Unattractive moths can afford to wait. Abstract : Individuals often have to balance the costs of risky behavior against the potential benefits they may gain from it. This trade-off is especially obvious in the interplay between natural and sexual selection because traits for mate attraction may attract predators as well. In the lesser wax moth Achroia grisella, ultrasonic sexual signaling comes with such a risk because calling for mates also attracts predatory bats. Attractive males should behave more cautiously than unattractive males under such circumstances, as they can expect more future mating opportunities and therefore have more to lose (the so-called asset protection principle). Contrary to these predictions, we found that pulse pair rate and peak amplitude, 2 song components attractive to females, correlated negatively with the duration of a silence response which is displayed when courtship song is experimentally overlayed with the search signal of a predator, the greater horseshoe bat. More attractive males thus recommence singing sooner than less attractive males. Although this is not in line with the asset protection principle, we discuss 3 different ways in which these distinct behavioral differences might be explained: 1) attractive males are in better condition and thus can more easily evade predators, 2) attractive signals are costly in terms of reduced life expectancy, and 3) risk-taking may in itself be a sexually selected trait and as such act as an honest signal of male quality.